PERAN FORUM GENRE KOTA DEPOK DALAM PENYELENGGARAAN PROGRAM SEKOLAH PRANIKAH - Puspa Rana, Diah Ayu; Sutarjo, Sutarjo; Suminar, Uum (IKIP Siliwangi, 2025)
Premarital school is a teaching and learning activity to improve knowledge and skills for unmarried men and women. It includes social, psychological, intellectual and sexual education. Premarital school is an effort to provide change or information, knowledge, skills and values ​​regarding future married life. Therefore, this research aims to describe the role of the Depok City Genre Forum in implementing the Premarital School program as well as the supporting and inhibiting factors for implementing the Premarital School program in the city of Depok. This research uses a case study method with a qualitative approach involving interviews, observation and documentation. The subjects of this research consisted of the head of the Youth Resilience sector from DP3AP2KB, the premarital school committee and premarital school participants. The results of the research show that the Depok City Premarital School succeeded in inviting and making them knowledgeable enough to think about whether marriage needs to be planned and whether they need to think carefully about their readiness to get married. Keywords: Premarital School, Genre Forum, Teenagers